19‐2: Strategies of Grayscale Enhancement for Scanning Light Field Display. Issue 1 (May 2016) - Su, Chen; Zhou, Xinxin; Li, Haifeng; Liu, Xu
Abstract : Due to the bilevel‐tone characteristic of the high‐speed projector, the grayscale and detail performance are limited in scanning light field display. We compare the display results processed by several state‐of‐the‐art halftone methods, which are generally applied for enhancing grayscale, and give the guidelines for the method choice.